Psychometric Properties and Construct Validity of the Short Version of the Self-Report Psychopathy Scale in a Southern European Sample. Issue 4 (3rd July 2020) - Seara-Cardoso, Ana; Queirós, Andreia; Fernandes, Eugénia; Coutinho, Joana; Neumann, Craig
Abstract: The Self-Report Psychopathy Scale–Short Form (SRP–SF) is a brief measure of psychopathy, developed via model-based test theory. The SRP–SF has a 4-factor structure with items reflecting affective, interpersonal, lifestyle, and antisocial domains, in line with the Psychopathy Checklist–Revised (PCL–R), which can be aggregated to form the traditional F1 and F2 dimensions of psychopathy. Previous research indicates the SRP is a viable tool for examining the prevalence of psychopathic propensities and their correlates in nonoffender populations. Currently, a substantial amount of nonoffender research on psychopathy is conducted in North America. Here, we inspect the psychometric properties of the SRP–SF and probe its association with general personality and empathy in a large southern European (Portuguese) community sample. Consistent with previous studies, results indicated good fit for the 4-factor model, including for separate female and male subsamples, good internal consistency across its scales and subscales, and the predicted pattern of associations with the correlates of psychopathy. The results of this cross-cultural study provide further evidence of the validity of the SRP–SF in the assessment of psychopathy in community samples, and help to extend the nomological net on the larger construct to a southern European sample.